O pojęciu „Rzeczpospolita" (res publica) w polskiej myśli politycznej XVI wieku - Pietrzyk-Reeves , Dorota (Czasopismo Prawno-Historyczne, 2010)
The paper argues that the concept of rzeczpospolita (commonwealth) can be seen as the key to the understanding of the main theories formulated by Polish political thinkers of the sixteenth century, and in particular such prominent writers as Andrzej Frycz Modrzewski, Wawrzyniec Goślicki, Sebastian Petrycy of Pilzno and Stanisław Orzechowski. The term res publica is closely connected with the classical republican tradition. Therefore the analysis of the concept rzeczpospolita presented in the paper begins with that tradition and its early modern revival before it goes on to examine Polish political thought of the sixteenth century and its potential affinity with the republican insight. One of the main theses of the paper is that the Polish reflection on rzeczpospolita includes the major categories of political philosophy that concern the nature and goals of a political community, its order and the arrangement of its political institutions, as well as the role and duties of its citizens and rulers. Examined from this perspective, Polish political thought of the sixteenth century can be seen as a valuable contribution to the modern republican tradition as it delineates the theoretical basis of the reflection on the political and legal order. Despite the fact that these categories were not strong enough to become a foundation for a strong state, they turned out to be the common ground and moral cement of Polish society in later periods.